2017
DOI: 10.1111/apps.12103
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Family Support, Parental Satisfaction, and Work–Family Conflict: Individual and Crossover Effects among Dual‐Earner Couples

Abstract: Workplace family support has been regarded as a factor that helps reduce individuals' work to family conflict (WFC). How this support translates into families' functioning is still to be determined. In this study, we used a systems perspective to examine (a) how perceptions of workplace family support affect parental satisfaction and consequently reduce WFC and (b) how the perception of support affects partners' parental satisfaction and WFC in dual‐earner couples. A two‐wave dyadic data set of dual‐earner cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 60 publications
4
47
0
Order By: Relevance
“…The positive crossover between satisfaction with family life and overall life satisfaction between the couple members may be explained by the interrelations between both partners, who share significant aspects of their lives, especially in the family domain [ 30 , 32 ]. Therefore, in this context, it is likely that direct crossovers occur among members of a couple, meaning that partners transmit or exchange experiences, affective states and resources through empathy [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive crossover between satisfaction with family life and overall life satisfaction between the couple members may be explained by the interrelations between both partners, who share significant aspects of their lives, especially in the family domain [ 30 , 32 ]. Therefore, in this context, it is likely that direct crossovers occur among members of a couple, meaning that partners transmit or exchange experiences, affective states and resources through empathy [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported either unidirectional crossover effects, from one partner to the other, or bidirectional effects, from one partner to the other and vice versa [ 31 ]. The bidirectional crossover requires special attention in dual-earner couples as both members of this dyad must balance work, family life and other roles, such as food-related tasks [ 32 ], and they must also fulfill different roles and tasks within their relationship [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spillover refers to the transmission of strain or positive experiences in one domain of an individual's life to another, whereas crossover involves the transmission of strain or positive experiences from one domain to another. However, the strain of positive experiences crosses over between people closely sharing the same environment (Matias et al, 2017). While some studies have focused on unidirectional crossover from husbands to wives, others have explored bidirectional crossover from husbands to wives and from wives to husbands (Westman & Bakker, 2008).…”
mentioning
confidence: 99%
“…While some studies have focused on unidirectional crossover from husbands to wives, others have explored bidirectional crossover from husbands to wives and from wives to husbands (Westman & Bakker, 2008). The bidirectional crossover influence is especially important in the case of dual-earner couples who share work and family experiences (Matias et al, 2017) and where the interdependence is recognised between individuals, structures, and processes (Kerr & Bowen, 1998). Westman and Vinokur (1998) proposed that crossover occurs directly when experiences, affective states, and resources are transmitted between the partners through empathy, while indirect crossover occurs through social interactions between partners.…”
mentioning
confidence: 99%
“…A well-researched area of in human resource management has been the study of the effect of HR practices on the work and family lives of individuals. Scholars have studied the work and life situations of dual-earner families for decades (Kossek and Nichols, 1992;Kossek, Colquitt, and Noe, 2001;Hammer, Neal, Newsom, Brockwood, & Colton, 2005;Park & Fritz, 2015;Matias, Ferreira, Vieira, Cadima, Leal, & Mena Matos, 2017;Crawford, Thompson, & Ashforth, 2019). With an increasing number of dual-career households, the demands of working time while simultaneously providing care for children or sick family members is a challenge faced by almost all employees today.…”
Section: Human Resource Practices and Work-family Conflictmentioning
confidence: 99%